Relational Animal Rights: Animals in the Framework of the Ecuadorian Constitution - Gutmann, Andreas (2024)
With the ruling in the Mona Estrellita case, the Constitutional Court of Ecuador has set an important precedent in relation to Animal Rights. With this judgment it clarifed that animals are subjects of rights under the framework of the Rights of Nature granted by art. 71 of the Ecuadorian Constitution. This clarifcation by the Court comes from a jurisprudential line that gives a systematic interpretation to the Rights of Nature. According to this jurisprudence, the Rights of Nature protect the ecosystemic processes of which animals are a part. Under this perspective the dispute between biocentrism and ecocentrism loses importance. There is no fundamental contradiction between the rights of (individual) animals and nature. From these principles a relational theory of animal rights can be deduced which departs from the ecological relationships that animals maintain with their environment. Based on these fundamentals, there are violations of Animal Rights, both through alterations of their ecosystemic environment and through acts that deprive animals of their environment, such as the capture and mistreatment of animals. Both behaviors affect the relationships that the animals have within an ecosystem.